An exploratory study of industry 4.0 in Malaysia: a case study of higher education institution in Malaysia - Mohd Arshad Mokhtar; Nurulhuda Noordin (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Industry 4.0 is defining as a smart factory through the emerging technology of the virtual and physical world as a collective term of technologies and concepts of value chain organization. The lack of understanding about Industry 4.0 concepts in Malaysia, especially from Higher Education Institution perspective, becoming an issue in Malaysia. Furthermore, industries in Malaysia are still relying on external expertise to implement Industry 4.0 in their environment with the expectation of an increase in productivity, efficiency, quality and to move away from foreign workers. This research aims to describe the relationship between technologies within Industry 4.0, people and the environment from the perspective of the Higher Education Institution in Malaysia and identify the problem of applying Industry 4.0 at the Higher Education Institution. Qualitative interviews were conducted with participants from an academic area and Industry 4.0 expert who has experience in both industry and academia. The Work System Framework is adopted in this research as a theoretical lens to extract the relevant information and deepen the understanding of applying Industry 4.0 at the Higher Education Institution in Malaysia. Results of this research reveal the problems faced by the Higher Education Institution in Malaysia towards applying Industry 4.0 in teaching and learning based on the relationship of people, technology and the environment. The results may contribute knowledge to the universities in preparation for future-ready graduates or talents as human capital for Industry 4.0 in Malaysia.